The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fendo.2021.684096
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Bias in Irritable Bowel Syndrome: Linking Steroids to the Gut-Brain Axis

Abstract: Irritable bowel syndrome (IBS) is a functional gastrointestinal disorder that is more common in females. Despite its high global incidence, the disease mechanism is still unclear and therapeutic options remain limited. The sexual dimorphism in IBS incidence suggests that sex steroids play a role in disease onset and symptoms severity. This review considers sex steroids and their involvement in IBS symptoms and the underlying disease mechanisms. Estrogens and androgens play important regulatory roles in IBS sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 229 publications
(243 reference statements)
0
20
0
Order By: Relevance
“…As some neurological disorders including IBS and autism demonstrate sex bias in incidence and severity (222) (261), sexually dimorphic effects of steroids (particularly sex hormones) has been suggested as a possible etiology. Neuroactive hormone abundance under normal physiological conditions is different in females and males.…”
Section: Sex Steroidsmentioning
confidence: 99%
See 2 more Smart Citations
“…As some neurological disorders including IBS and autism demonstrate sex bias in incidence and severity (222) (261), sexually dimorphic effects of steroids (particularly sex hormones) has been suggested as a possible etiology. Neuroactive hormone abundance under normal physiological conditions is different in females and males.…”
Section: Sex Steroidsmentioning
confidence: 99%
“…This could be due to estrogen potentiating TRPV1 channel activity (270), which contributes to pain sensation and is upregulated in IBS (4). Furthermore, sex steroids regulate the serotonergic system (222), which could also explain why sex dependence is evident in alterations of the serotonergic system in IBS, which is another signal associated with pain (168). Despite the lack of consistency in IBSassociated microbiome signatures, the gut microbiota could mediate the effect of steroids in IBS pathogenesis.…”
Section: Irritable Bowel Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…Clinical observations have found that women tend to have slower gastrointestinal (GI) transit and are more prone to constipation than men. However, previous studies have obtained contradictory findings regarding the effect of the various sex hormones on GI motility (25)(26)(27). A recent study based on female dihydrotestosterone (DHT)-treated PCOS rats found lower maximal colon muscle contractility in response to acetylcholine stimulation in DHT-treated rats than in untreated rats (28).…”
Section: Discussionmentioning
confidence: 99%
“…These immune responses could also underpin differences in COVID-19 vaccine efficacy. Sex steroids are known to regulate the gut microbiota ( Manosso et al, 2021 , So and Savidge, 2021 ) and thus could mediate vaccine efficacy through the gut microbiota. As such studies are warranted that would investigate the role of the gut microbiota in gender differences in COVID-19 vaccine efficacy.…”
Section: Intestinal Dysbiosis Linking Risk Factors To Inefficacy Of Covid-19 Vaccinesmentioning
confidence: 99%